2014
DOI: 10.1016/j.pjnns.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Phantom phenomena and body scheme after limb amputation: A literature review

Abstract: Phantom phenomena are subject of various, often inconsistent, descriptions, and new concepts and treatment approaches emerge. The aim of the study is to describe contemporary terminology and developments in the field, and to share personal experience. A review of English and French language literature, published prior to 27th February, 2012, extracted from PubMed/MEDLINE, Google.fr, GoogleScholar databases, and by hand searching of selected full text papers and textbooks with correspondence to personal clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…Proximal amputations are associated more frequently with PLP than are distal amputations. 1 By their nature, the hemipelvectomy and the forequarter amputation are much more painful procedures with more difficult recovery periods. Patients who undergo those surgeries are expected to require higher consumption of pain medications than are those who undergo more distal amputations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Proximal amputations are associated more frequently with PLP than are distal amputations. 1 By their nature, the hemipelvectomy and the forequarter amputation are much more painful procedures with more difficult recovery periods. Patients who undergo those surgeries are expected to require higher consumption of pain medications than are those who undergo more distal amputations.…”
Section: Discussionmentioning
confidence: 99%
“…1 According to the literature, 60% to 90% of amputees experience PLP at some point in their lifetime. 2 Phantom limb pain can occur whether the amputation is traumatic or surgical, and the incidence is generally higher after a traumatic loss or if there is a pre-existing painful condition, as opposed to a planned surgical amputation of a non-painful limb.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PLP-pain perceived to originate from an absent body part after amputation-represents the symptomatic end manifestation of ectopic inputs along this transformed pathway (19)(20)(21). Numerous studies have reported on interventions at different points along this altered pathway, from direct and indirect cortical modulation to surgical resection of the distal residual nerve (and at many points in between), yet no accepted guidelines for treatment have emerged (21)(22)(23)(24)(25)(26). Treatment strategies targeting the peripheral nerve, such as catheter placement for infusion of anesthetic postoperatively, peripheral neuromodulation, lidocaine injections, and cryoanalgesia guided by nerve stimulation, have been reported more recently as potentially efficacious (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%